Animated Instructional Medium in Structural Foundation - Daradar, Maricel (JPAIR Multidisciplinary Research, 2022)
Complicated concepts in designs are difficult to explain in traditional media, such as still slides. Animation seems to provide an advantage in delivering a better rendition of these concepts. This study aimed to develop an Animated Instructional Medium in Structural Foundation, which could be used by Drafting Technology Students of Carlos Hilado Memorial State College, Talisay, Negros Occidental and will serve as a viable instructional material in teaching drafting technology subjects. Specifically, it sought to design and develop an Animated Instructional Medium in Structural Foundation with the following features: animated, interactive, and quality. It also determined the acceptability of the project in terms of animation, user control, interactivity, and images. Moreover, formulate an instructional guide for using the project. Descriptive and developmental methods were used in this study involving one hundred forty respondents comprising architects, civil engineers, drafting instructors, and students for project evaluation. The findings of the study showed that the Animated Instructional Medium in Structural Foundation was rated highly acceptable in terms of technical features and very acceptable in terms of animation, user control, interactivity, images, and text.  An instructional guide was formulated to serve as an instructional medium for teaching basic structural foundations in Architectural Drafting. This study is beneficial to the BSIT Drafting students, construction foremen, construction workers, homeowners, instructors, and researchers.
Keywords: Education; Architectural Drafting; Instructional Material; descriptive and developmental design; Philippines